Survey Study on the Prevalence of Cutaneous Leishmaniasis in Iraq - Al-Obaidi , Mohammed J.; Al-Obaidi , Mohammed J.; Al-Hussein , Mohammed Yaseen Abd; Al-Hussein , Mohammed Yaseen Abd; Al-Saqur, Ihsan M. (Iraqi Journal of Science, 2022)
Human cutaneous leishmaniasis (CL) is caused by Leishmania sp. parasite and endemic in Iraq. The current study was including analysis of available database from Iraqi CDC to determine the distribution of CL cases for the period (2008-2015 years) in Iraq. Total reported cases for this period were 17001 (range 2.9-10.5 per 100,000 individuals). Highest reported cases were recorded in the year 2015 (4000 cases). Male infections cases of CL (50.8%) were more than female infections (49.2%). Highest infections of CL were observed in the age group (5-14yr.) as (34.6%), While the lowest infection of CL were observed in the age group (>1yr.) as (4.3%). Highest infection case of CL was observed in the middle and west of Iraq (53%). In contrast, the lowest reported cases of CL were observed in the North of Iraq (1%). Monthly distribution of CL in winter was more than in summer months. This study concluded that the CL cases in continuously increasing. The aim of the study is to monitor the causes of CL distribution in Iraq.